Frontispiece: ortho‐Fluoroazobenzenes: Visible Light Switches with Very Long‐Lived Z Isomers. Issue 50 (8th December 2014) - Knie, Christopher; Utecht, Manuel; Zhao, Fangli; Kulla, Hannes; Kovalenko, Sergey; Brouwer, Albert M.; Saalfrank, Peter; Hecht, Stefan; Bléger, David
<x xml:space="preserve">Abstract</x> Photochromism In their Full Paper on page 16492 ff, A. M. Brouwer, P. Saalfrank, S. Hecht, D. Bléger, and co‐workers present the design and synthesis of ortho‐fluoroazobenzene visible light switches together with a detailed analysis of their outstanding properties, with a particular emphasis on the remarkable thermal stability of the Z isomers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>